Depression and HIV Infection are Risk Factors for Incident Heart Failure Among Veterans: Veterans Aging Cohort Study. - White, Jessica R; Chang, Chung-Chou H; So-Armah, Kaku A; Stewart, Jesse C; Gupta, Samir Kumar; Butt, Adeel A; Gibert, Cynthia L; Rimland, David; Rodriguez-Barradas, Maria C; Leaf, David A; Bedimo, Roger J; Gottdiener, John S; et al. (Circulation, 2015)
-Both HIV and depression are associated with increased heart failure (HF) risk. Depression, a common comorbidity, may further increase the risk of HF among HIV+ adults. We assessed the association between HIV, depression and incident HF.